What Institutions help immigrants Integrate? - Peter Huber (WWWforEurope, 2015)
I analyse the importance of national migration policy and labour market institutions for immigrants labour market integration. Results indicate that the sending country structure of immigrants to a country, its ethnic diversity and its wage bargaining institutions as well as product market regulation are the most important national institutions impacting immigrants labour market integration. Variables related to the generosity of the welfare state and tax progressivity are, by contrast, only important in selecting migrants with high employment probabilities and migration policy variables remain unimportant altogether. Countries with more centralized wage bargaining, stricter product market regulation and countries with a higher union density, have worse labour market outcomes for their immigrants relative to natives even after controlling for compositional effects. Immigrants with better chances for labour market integration on account of observable characteristics self-select to countries with more centralised wage bargaining and higher minimum wages but a lower coverage rate by collective agreements. Liberal product market regulation, less centralised wage bargaining and ensuring inclusive trade unions thus assist the integration of immigrants in host countries labour markets most strongly.
Keywords: J15; J61; 330; Immigrant Integration; Migration Policy; Labour Market Institutions